2006
DOI: 10.1088/1748-6041/1/4/001
|View full text |Cite
|
Sign up to set email alerts
|

Attachment and growth of human bone marrow derived mesenchymal stem cells on regenerated antheraea pernyi silk fibroin films

Abstract: Silk fibroin of the silkworm Bombyx mori has been studied extensively, while the research on Antheraea pernyi silk fibroin (A. pernyi SF) in biomaterials is only at an early stage. In this study, the attachment, morphology, growth and phenotype of human bone marrow derived mesenchymal stem cells (hBMSCs) cultured on the regenerated A. pernyi SF films were studied in vitro. The results indicated that the attachment of hBMSCs on the regenerated A. pernyi SF films was almost the same as that on the collagen films… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 43 publications
3
33
0
Order By: Relevance
“…Compared with B. mori silk fibroin, the results showed that Ap-SF readily allowed cell attachment and growth. By studying the attachment, morphology, growth and phenotype of human bone marrow derived mesenchymal stem cells (hBMSCs) cultured on Ap-SF films, it was found that Ap-SF, such as B. mori silk fibroin and collagen, could support hBMSC attachment, growth and phenotypic maintenance, and has better biocompatibilities for in vitro culture of hBMSCs [12]. Based on these features, interest has risen in the use of Ap-SF as a starting material for advanced biomedical applications such as cell culture substrates, surgical mending materials and tissue engineering scaffolds [13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with B. mori silk fibroin, the results showed that Ap-SF readily allowed cell attachment and growth. By studying the attachment, morphology, growth and phenotype of human bone marrow derived mesenchymal stem cells (hBMSCs) cultured on Ap-SF films, it was found that Ap-SF, such as B. mori silk fibroin and collagen, could support hBMSC attachment, growth and phenotypic maintenance, and has better biocompatibilities for in vitro culture of hBMSCs [12]. Based on these features, interest has risen in the use of Ap-SF as a starting material for advanced biomedical applications such as cell culture substrates, surgical mending materials and tissue engineering scaffolds [13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…35 Similarly, non-mulberry silk fibroin-based materials from the Samia ricini and Antharae pernyi silkworms have supported fibroblast-like, osteoblast-like, and bone marrow-derived mesenchymal stem cell growth in vitro. 42,43 In this study, we demonstrated the cytocompatibility of Spidrex, showing that primary human and rat tenocyte viability increased over 14 days of culture on Spidrex. Morphological analysis of calcein-AM-stained human tenocytes cultured on the different silk scaffolds and within collagen gels demonstrated that human tenocytes retained their native elongated morphology when cultured on Spidrex, whereas human tenocytes cultured on the knitted B. mori scaffold and within the collagen gels did not appear as tenocytic.…”
Section: Figmentioning
confidence: 55%
“…[32][33][34] Studies evaluating silk as a biomaterial for tendon regeneration have largely focused on the mulberry B. mori silk or composites of B. mori silk with either synthetic polymers or collagen. 28,29,[35][36][37][38] However, given that non-mulberry silks contain the cell binding RGD tripeptide motif, [39][40][41] and have been shown to support fibroblast-like and bone marrow-derived mesenchymal stem cell growth in vitro, 42,43 non-mulberry silk-derived scaffolds hold much promise as biomaterials for enhancing tendon tissue regeneration. 44 In this study, in vitro assays were used to assess the cytocompatibility and immunogenicity of a novel knitted, nonmulberry silk fibroin scaffold designed for use in tendon tissue regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…From its commercial use, decades ago, as a biomedical suture, to today's tissue engineering scaffolds, SF has been studied as an ideal biomaterial for a range of applications, including tissue repair and induction of tissue regeneration. Many studies have revealed that silkworm SF, such as B mori SF in various shapes (such as fibers, films, nets, mats, and sponges), can support the adhesion and proliferation of many kinds of cells, including keratinocytes, fibroblasts, vascular endothelial cells, epithelial cells, bone marrow stromal cells and neuroglia cells [1][2][3][4][5][6][7][8] . In particular, stem cellbased tissue engineering with B mori SF has expanded the use of silk-based biomaterials for bone, ligament, cartilage and connective tissues [1][2][3][4] .…”
Section: Introductionmentioning
confidence: 99%
“…The SF from the wild silkworm A pernyi or A mylitta has attracted much attention as biomaterials due to a functional Arg-Gly-Asp (RGD) tripeptide sequence [7,8] . The RGD tri-peptide, found within fibronectin, laminin, vitronectin, collagen and other related adhesion molecules in extracellular matrix (ECM) proteins, has been discovered to be a recognition site for adhesion, spreading and motility of cells [9,10] .…”
Section: Introductionmentioning
confidence: 99%